TRANSIENT ANALYSIS OF A COMPRESSED AIR ENERGY STORAGE SYSTEM - Pérez-Trujillo, Juan; Kowalski, Gregory; Elizalde-Blancas , Francisco (MATTER: International Journal of Science and Technology, 2017)
A transient energy analysis was performed in a Compressed Air Energy Storage (CAES) system. The aim is to perform a parametric analysis to determine the efficiency and output energy depending on some designparameters as the number of tanks connected in parallel, the insulation thickness, the storage time and the outflow. Mass and energy balanceswere carried out on every component of the system,the resulting equationsfrom the analysis weresolved numerically using the explicit Euler’s method. The system operating forashort storage timepresentsa higher efficiency (about 42.38%) with insulated tanks, however it is lower (about 23.54%) for long storage timeandnon-insulatedtanks. Nevertheless, when the system with insulated tanks reaches the steady state, i.e., for long storage time, its efficiency is almost half that onewith tanks without insulation, 11.5% and 23.54%, respectively. These results indicate that for short storage times is better to insulate the tanks and for longer storage times is more convenient no insulation